Twistacene functionalized anthracenes with high-efficiency blue fluorescence. (February 2016) - Ren, Tiejun; Song, Minshun; Zhao, Jianwen; Wang, Wenying; Shen, Xingxing; Gao, Chang; Yi, Yuanping; Xiao, Jinchong
Abstract: Two novel 9, 10-diarylanthracene derivatives containing small twistacenes units (9, 14-diphenylbenzo[f]tetraphene and 2, 7-di-tert-butyl-9, 14-diphenyldibenzo[de, qr]tetracene) have been successfully synthesized and characterized. The resulting molecules show high thermal decomposition temperatures (5% weight) of 443 °C–516 °C, and emit strong fluorescence in dichloromethane and thin film with full widths at half maximum of ca . 55 nm, falling into blue region. The organic light-emitting diodes doped with them into 3, 3′-di(9H-carbazol-9-yl)-1, 1′-biphenyl were prepared and showed the maximum luminescence in the range of 1784–4122 cd/m 2 respectively, which indicates these new diarylanthracene derivatives are appealing fluorescent dyes for OLEDs. Graphical abstract: Two novel anthracene derivatives containing the twistacenes were synthesized for use as active layers in blue organic light emitting diodes. Highlights: Two twistacene functionalized anthracenes were synthesized. The obtained molecules show high thermal stability and strong blue fluorescence. The fabricated devices exhibit good electroluminescent performance.